First Report of Tomato yellow leaf curl virus in Tomato in Mauritius - Lobin, K (Plant disease, 2010)
Tomato is a food crop of economic importance in Mauritius. It is grown in open fields and in greenhouses by more than 4,500 small- and large-scale growers throughout the island. Open-field tomatoes are mostly a cooking type, while those produced in greenhouses are salad types. Acreage under production is approximately 900 ha with an annual production of approximately 11,500 tons. In September 2009, plants with reduced leaf size, leaf curling, and yellow margins associated with plant dwarfism were observed in open-field tomato crops in the southern part of the island. Whitefly populations were observed in these fields. These symptoms were suggestive of infection with a leaf curl-causing begomovirus such as Tomato yellow leaf curl virus (TYLCV) (family Geminiviridae, genus Begomovirus). Similar symptoms caused by TYLCV were reported in neighboring Reunion Island in 1997 (1). In October 2009, 3.15 ha of tomato were surveyed in the south at la Flora, Camp diable, L'escalier, Plein Bois, and Plaine Magnien to monitor the disease. Symptomatic plants were observed in all areas surveyed and disease incidence ranged from 5 to 50%. The disease was more prevalent in tomato 'Swaraksha' and 'Epoch', which are widely cultivated. Seventeen symptomatic leaf samples from La flora, Camp Diable, L'escalier, Plein Bois, and Plaine Magnien areas were collected for begomovirus detection by PCR. Total DNA was extracted and tested using AV494 (5'-GCC YAT RTA YAG RAA GCC MAG-3') and AC1048 (5'-GGR TTD GAR GCA TGH GTA CAT G-3') primers from the core region of the coat protein that detect most begomoviruses (2). Seventeen of 17 samples (100%) gave an amplicon of expected size. PCR amplicons from selected samples were cloned and sequenced. The consensus sequence was assembled, and the sequence (GenBank Accession no. HM448447) had 100% identity with nucleotides 458 to 1,036 of the Almeria isolate (GenBank Accession no. AJ489258), an isolate from the Netherlands (FJ439569), Morocco (EF060196), and Spain (AJ519441), and nucleotides 451 to 1,029 of the RE4 isolate from Reunion Island (AM409201). On the basis of the initial sequence obtained, specific primers (RM-TYLCV 583C: 5'-CCA CGA GTA ACA TCA CTA ACA-3' and RM-TYLCV 895F: 5'-GGA ACA GGC ATT AGT TAA GAG-3') were designed to amplify the remainder of the genomic sequence by PCR followed by cloning and sequencing of the amplicons. At least three clones were sequenced to arrive at the consensus sequence. Sequence comparisons showed that the TYLCV isolate from Mauritius had the greatest sequence identity (95 to 100%) with the above isolates. To our knowledge, this is the first report of TYLCV in tomato in Mauritius. In view of the economic importance of leaf curl disease in tomato in many parts of the world, an island-wide survey needs to be carried out to monitor the disease and assess its impact on tomato production. References: (1) M. Peterschmitt et al. Plant Dis. 83:303, 1999. (2) S. D. Wyatt and J. K. Brown. Phytopathology 86:1288, 1996